Pyrimidine-fused heterocycle derivatives as a novel class of inhibitors for α-glucosidase. (December 2013) - Yousefi, Reza; Alavian-Mehr, Mohammad-Mehdi; Mokhtari, Fatemeh; Panahi, Farhad; Mehraban, Mohammad H.; Khalafi-Nezhad, Ali
<x xml:space="preserve">Abstract</x> The needs for diverse inhibitors of α-glucosidase (α-Gls) encouraged us to synthesize five different poly-hydroxy functionalized pyrimidine-fused heterocyclic (PHPFH) molecules, having either aliphatic or aromatic side chains (C1–C5) and their inhibitory activities were examined spectroscopically against yeast and mouse intestinal α-Gls. The results revealed that aromatic substitution of the synthetic compounds has significant impact on their inhibitory properties. Moreover C3 with the substituted moiety as 4-(4-aminophenylsulfonyl) phenyl (4-APSP) revealed strong inhibitory activity with non-competitive and competitive inhibition modes against yeast and mouse α-Gls, respectively. Furthermore, in the presence of increasing concentration of C3, both Trp and 1-anilinonaphthalene-8-sulfonic acid (ANS) fluorescence intensities of yeast α-Gls were gradually decreased, suggesting that C3 binding induced significant structural alteration which was accompanied with the reduction of hydrophobic surfaces. Also, the interaction between yeast α-Gls and C3 was proved to be spontaneous and driven mainly by hydrophobic forces. Overall, this study suggests that aromatic substitution on pyrimidine-fused heterocyclic (PFH) scaffold may represent a novel class of promising inhibitors of α-Gls.